Performance of carbon fibre concrete subjected to fire. (2021) - Khaleel, Omar R.; Al Wahaibi, Mahmood M.S.; Abed, Mohammed J.; Dawood, Mahmoud; Fayyadh, Moatasem M.
Abstract: Polyacrylonitrile carbon fibre is one of the fibres that can be used in civil engineering applications. It is also called carbon graphite and graphite fibre. These types of fibre contain a large number of carbon filament sets. The objective of this study is to investigate the effect of carbon fibre on the resistance of concrete to fires that could occur in concrete structural elements. This study used two percentages of carbon fibre that were added to concrete mixes using 1% and 2% of cement. Three mixes were made: normal concrete (NC), 1% carbon fibre concrete (1% CFC) and 2% carbon fibre concrete (2% CFC). Six tests were conducted to evaluate the performance of the concrete mixes: the slump test, the compressive strength test (before and after exposure to fire), the flexural strength test, the thermal conductivity test and the rebound hammer test. The test results showed that 1% CFC exhibited higher compressive strength when subjected to fire and high temperatures compared to the other mixes. Moreover, the addition of 2% of carbon fibre reduced the compressive strength to an even lower level than that of the normal concrete mix.